Special Environment for Teaching Students with ASD in Creative Profession - E.V. Khilkevich; A.S. Steinberg; A.V. Khaustov (Moscow State University of Psychology and Education, 2022)
Currently, the proportion of students with autism spectrum disorders (ASD) at levels of secondary vocational and higher education is extremely small, but the proportion of students with ASD in general education is increasing every year. This makes problems of vocational guidance for applicants and considering special educational needs in the process of further education in universities and secondary vocational schools more and more urgent. An analysis of the experience of graduates of the Federal Resource Center for Organization of Comprehensive Support to Children with Autism Spectrum Disorders and some successful cases of employment, as well as existing legal documentation, allows us to conclude that the choice of creative professions as a future employment for this category of students is very promising. Such professions can become a direction for career guidance of creatively gifted young people with ASD, both with intact intellect and with intellectual disabilities. The basis for obtaining a profession in colleges and universities should be a set of implementations of special learning conditions that contribute to the successful inclusion of students with special needs in the educational environment.